Identifying conflict and violence in micro-level surveys - Tilman Brück; Patricia Justino; Philip Verwimp; Alexandra Avdeenko (Institute for the Study of Labor (IZA), 2010)
The overall goal of the report is to increase the capacity of researchers and policy makers to identify comparatively, and across time, how individuals, households and communities are affected by violent conflict. The report provides an extensive overview of existing practices and datasets used in this field of research. We investigate existing methodologies and data-bases used to operationalize the variables of interest and discuss the channels linking violent conflict to individual and household welfare. Special attention is paid to methodological issues on how to design a module and operationalize variables that allow researchers to analyze the welfare effects of violent conflict across countries and across time. We develop and discuss a generic household module that can be easily inserted into future socio-economic surveys implemented in conflict-affected countries. This module will enable researchers to address specific violence-related issues comparatively across different conflict settings and systematically across time. The module proposed builds on previous experiences on survey designs in conflict-affected areas. We review existing conflict- and violence-related questionnaires, with a special focus on World Bank's Living Standard Measurement Surveys (LSMS), and propose suggestions on how to improve questionnaires in order to deepen the understanding of the nature of violent conflict and the channels whereby conflict and violence affect the welfare characteristics and choices of individuals and households in conflict areas.
Keywords: C81; D74; F52; O12; 330; conflict; violence; war; individuals; households; survey; questionnaire; methodology; Gewalt; Konflikt; Krieg; Privater Haushalt; Wohlfahrtseffekt; Lebensstandard; Schätzung; Welt